2020
DOI: 10.2147/rrtm.s190300
|View full text |Cite
|
Sign up to set email alerts
|

<p>The State of Affairs in Post-Exposure Leprosy Prevention: A Descriptive Meta-Analysis on Immuno- and Chemo-Prophylaxis</p>

Abstract: Objective: Annually, over 200,000 people are diagnosed with leprosy, also called Hansen's disease. This number has been relatively stable over the past years. Progress has been made in the fields of chemoprophylaxis and immunoprophylaxis to prevent leprosy, with a primary focus on close contacts of patients. In this descriptive meta-analysis, we summarize the evidence and identify knowledge gaps regarding post-exposure prophylaxis against leprosy. Methods: A systematic literature search according to the Prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 105 publications
(254 reference statements)
0
27
0
Order By: Relevance
“…Here, we showed the protective effect of BCG vaccination (previous vaccination as measured by the presence of a scar), revaccination or recent primary dose, independently of others factors like clinical form of the index case and consanguinity. Meta-analysis studies showed that an additional dose of BCG was more protective in the prevention of leprosy, suggesting an important strategy in areas where leprosy continues to be a public-health problem [31][32][33] . The protection is higher in household contacts of leprosy patients, but evidence for the benefit of re-vaccination is conflicting 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed the protective effect of BCG vaccination (previous vaccination as measured by the presence of a scar), revaccination or recent primary dose, independently of others factors like clinical form of the index case and consanguinity. Meta-analysis studies showed that an additional dose of BCG was more protective in the prevention of leprosy, suggesting an important strategy in areas where leprosy continues to be a public-health problem [31][32][33] . The protection is higher in household contacts of leprosy patients, but evidence for the benefit of re-vaccination is conflicting 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Brazilians were reportedly told, "There is leprosy in your area, and that is why we offer people preventive treatment against leprosy" when being informed about the Leprosy post-exposure prophylaxis (LPEP) study, without indicating the temporary and partial effect of singledose rifampicin. 5 The definition of contacts in this study differed from that in the COLEP cluster randomised controlled trial in Bangladesh. 6 In Richardus and colleagues' study, contacts were given single-dose rifampicin up to 2 years after diagnosis of the index case; whereas, in the COLEP study, singledose rifampicin was given to contacts of newly diagnosed index cases.…”
Section: Leprosy Post-exposure Prophylaxis Risks Not Adequately Assessedmentioning
confidence: 90%
“…However, field trials of BCG as a vaccine for leprosy have yielded widely variable results (reviewed in ref. 125,126 Other whole cell vaccine candidates for leprosy include M habana , M vaccae , M indicus pranii , and ICRC bacilli 127…”
Section: Contributions Of the Mouse Modelmentioning
confidence: 99%